efecto del desmane sobre el peso del racimo y las dimensiones del fruto del hibrido de platano FHIA 21 (Musa AAAB) - Delgado, E.=700 1 Gonzalez, O.; Moreno, N.; Romero, D.
(En, Es)
ilus., 15 ref.
Keywords: MUSACEAE; METODOS DE CULTIVO; PODA; INFLORESCENCIAS; VENEZUELA; MUSACEAS; PRACTICAS AGRONOMICAS; DESMANE